IADC/SPE Drilling Conference 2008
DOI: 10.2118/112731-ms
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Deep Drilling Performance with Improvements in Drill Bit and Drilling Fluid Design

Abstract: Full-scale laboratory testing was conducted under a joint industry and Department of Energy program titled "Optimization of Deep Drilling Performance; Development and Benchmark Testing of Advanced Diamond Product Drill Bits and HP/HT Fluids to Significantly Improve Rates of Penetration." In total, seven bits and twelve different drilling fluids were tested in three different rocks at a variety of drilling parameters. Phase 1 results have been reported in a previous paper (Arnis Judzeis et al., 2007). This pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…Whitfill et al (2002) showed by review of field data that penetration rates in salt formations tended to be higher with synthetic based fluids than water based fluids. There is abundant evidence that drilling fluid composition influences the drilling process and drilling efficiency under otherwise constant borehole pressure and operating parameters, for instance as indicated recently by Black et al (2007) and Curry et al (2008). These latter studies showed markedly higher penetration rates and lower mechanical specific energy levels with PDC bits in Crab Orchard sandstone, a hard and tight sandstone, and Mancos shale, a moderately hard and relatively water insensitive shale, when drilled with base oil than when drilled with an invert emulsion field mud based on the same fluid but containing brine emulsion droplets, weighting material, viscosifying and fluid loss control agents.…”
Section: Discussionmentioning
confidence: 97%
“…Whitfill et al (2002) showed by review of field data that penetration rates in salt formations tended to be higher with synthetic based fluids than water based fluids. There is abundant evidence that drilling fluid composition influences the drilling process and drilling efficiency under otherwise constant borehole pressure and operating parameters, for instance as indicated recently by Black et al (2007) and Curry et al (2008). These latter studies showed markedly higher penetration rates and lower mechanical specific energy levels with PDC bits in Crab Orchard sandstone, a hard and tight sandstone, and Mancos shale, a moderately hard and relatively water insensitive shale, when drilled with base oil than when drilled with an invert emulsion field mud based on the same fluid but containing brine emulsion droplets, weighting material, viscosifying and fluid loss control agents.…”
Section: Discussionmentioning
confidence: 97%
“…One is to maintain focus on bit torque instead of WOB when drilling with PDC bits. Torque translates directly to ROP for a given rotary speed (Black, et al, 2008), and a target value of 5,000 ft-lb has been used with great success. A second lesson is to mitigate stick-slip by decreasing WOB instead of increasing RPM beyond 120 RPM when drilling hard, abrasive rock; the loss of instantaneous ROP while drilling a few feet of hard rock is usually regained in the softer rock beneath it by preserving the cutting structure.…”
Section: Postwell Analysismentioning
confidence: 99%
“…Phase-2 laboratory drilling tests were conducted and reported (Black et al 2008;Black and Judzis 2003). These tests set out to examine the impact of several factors including alternative drilling-fluid chemistries and weighting materials; PDC-bit-design options, such as bit profile and blade count, and impregnated-bit-grit size.…”
Section: Impact Of Bit Design and Mud On Ropmentioning
confidence: 99%
“…The rock tested was the same as during the first phase. The results of the second phase are provided, were published, and presented in 2008 (Black et al 2008;Black and Judzis 2003).…”
Section: Introductionmentioning
confidence: 99%